The human indigenous microbiota - Relman, David (Henry Stewart Talks, 2009)
Benefits derived from our microbiota, Clinical problems associated with the indigenous microbiota, Degradation of fitness landscape, Phylogenetic surveys, Patterns of microbial diversity in the human body, Site-specific distributions of bacterial phyla in healthy humans, Skin microenvironments, Ecological boundaries, Rarefaction curves, What are the factors that regulate or restrict human indigenous microbial diversity?, What are the features of early microbial colonization in the human body?, Early days: evidence of opportunistic exposures, Later days: emergence of individuality, Features of indigenous microbial diversity in mammals, Families have more functionally similar microbiomes, Challenges and future directions
Updated at 2010/08/11